A novel human autoantigen, endothelial cell growth factor, is a target of T and B cell responses in patients with Lyme disease. Issue 1 (27th December 2012) - Drouin, Elise E.; Seward, Robert J.; Strle, Klemen; McHugh, Gail; Katchar, Kianoosh; Londoño, Diana; Yao, Chunxiang; Costello, Catherine E.; Steere, Allen C.
Abstract: Objective: Autoantigen presentation by HLA–DR molecules is thought to be a central component of many autoimmune diseases, but identifying disease‐relevant autoantigens has been a difficult challenge. In this study we aimed to identify autoantigens in patients with antibiotic‐refractory Lyme arthritis, in which infection‐induced autoimmunity is thought to play an important role. Methods: Using tandem mass spectrometry, naturally presented HLA–DR self peptides from a patient's synovium were identified, synthesized, and reacted with his peripheral blood mononuclear cells (PBMCs). Immunoreactive peptides and their source proteins were then tested for T and B cell responses using large numbers of patient cells or sera. Results: Of 120 HLA–DR–presented self peptides identified from one patient, one peptide derived from endothelial cell growth factor (ECGF) caused his PBMCs to proliferate. T and B cell responses to ECGF occurred systemically in ∼10–30% of patients with early or late manifestations of Lyme disease, primarily in those with refractory arthritis–associated HLA–DR alleles, such as DRB1*0101 and 0401. Compared with patients with antibiotic‐responsive arthritis, those with antibiotic‐refractory arthritis had significantly higher concentrations of ECGF in synovial fluid ( P < 0.0001) and more often had ECGF antibody reactivity. Among non–antibiotic‐treated historical patients who developed arthritis, 26% had ECGF reactivity, which often developed before the onset of arthritis and was associated with significantly longer courses of arthritis. Conclusion: T and B cell responses to ECGF occur in a subset of patients with Lyme disease, particularly in those with antibiotic‐refractory arthritis, providing the first direct evidence of autoimmune T and B cell responses in this illness.